Determinants of Career Change: A Literature Review - Uy, Jeffrey (JPAIR Multidisciplinary Research, 2020)
A recent study found that 49% of employees had change careers from a wide range of industries. However, most successful career switchers take years to learn new skills, network and be financially prepared. The study uses the literature review as a means to examine available scientific literature on the demographic characteristics, personal, and organizational factors as determinants of a career change. The content analysis of scientific literature was used. The sources came from research databases such as google scholar, directory of open access journals, PubMed, and other websites. The findings suggest that demographic characteristics, personal, and organizational factors are determinants of a career change.